TEACHER’S INNOVATION IN IMPROVING CHILDREN’S COGNITIVE ASPECT - Sarah, Sitti; Darmiyati, Darmiyati; Mujiyat, Mujiyat (E-CHIEF Journal, 2023)
The currect problem that takes place is the low cognitive abilities of children in Group B of Kindergarten Kenanga Banjarmasin in solving everyday problems and acting creatively. Efforts to improve developmental activities and outcomes, particularly through a combination of direct instruction, demonstration, problem-based learning, and experimentation were done. This study aims to analyse teacher activities, children's activities, and children's development outcomes. Three meetings were used to conduct the qualitative classroom action research (CAR) portion of this study. Ten children from Group B of Kindergarten Kenanga Banjarmasin were used as research subjects. The research results showed that the teacher's activities received a score of 22 for quite good criteria at meeting I and a score of 34 for very good criteria at meeting III. 40% of children's activity occurs at meeting I, 60% at meeting II, and 100% at meeting III. At the first meeting, the child's cognitive development was 40 percent, and at the third meeting, it was 100 percent.